Efektifitas Penggunaan Buku Cerita Bergambar terhadap Kecerdasan Visual Anak Prasekolah - Eka Mei Ratnasari (Universitas Trunojoyo Madura, 2020)
Multiple intelligences must be optimally stimulated. Its development will be very good for the development of early childhood abilities. This research will discuss the effectiveness of the use of picture books on preschool children's visual intelligence. The research aims to look for the effectiveness of the use of picture books on children's visual intelligence aged of 4-5 years. This study used quasi-experiment method. The subjects were children of TK-KB ABA Pringwulung, Yogyakarta. The sampling technique uses purposive sampling, including two groups, A1 as the experimental group and A2 as the control group. The subjects used in this study examined 40 children. The data analysis technique used a t-test using the SPSS for Windows version 16 computer program to see children's visual intelligence between the two cohorts. The results indicated that there was a significant impact on children's visual intelligence through the use of picture book media in group A at TK-KB ABA Pringwulung Yogyakarta. It can be used by parents, educators, and educational practitioners so as to build an appropriate strategy in developing early childhood visual intelligence.